Faktor-faktor Mendorong Alih Fungsi Lahan dan Dampaknya terhadap Produksi Beras di Kabupaten Tabanan, Provinsi Bali - I PUTU GEDE ADHI KRISNA KARTIKA PRATAMA; WIDHIANTHINI WIDHIANTHINI; A.A.A. WULANDIRA SAWITRI DJELANTIK (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2021)
Factors driving land use change and its impact on rice production in Tabanan Regency, Bali Province Rice land conversion in Tabanan Regency, Bali Province increases every year. This has an impact on the sustainability of rice production in Tabanan Regency. This study aims to identify the factors that encourage farmers to convert their rice land and assess the sustainability of rice production in Tabanan Regency. This research took place from June to September 2020. The sample in this study includes 54 farmers consisting of 6 farmers from each sub-district who own rice land in the village with the highest level of rice land conversion in their sub-district. Farmers are grouped into two groups, namely farmers who have carried out a rice land conversion and farmers who have not carried out a rice land conversion. The analysis used was logistic regression analysis, paired t-test and Multidimensional Scaling (MDS) analysis. The results show that there are five variables that significantly influence the occurrence of rice land conversion, namely farming income, farmer formal education, farmer age, farmers' access to labor, and agricultural extension. From the economic and socio-cultural aspects, rice production is quite sustainable, but from the institutional dimension it is not. Overall, when viewed from the three aspects, rice production is classified as quite sustainable. Special attention is needed to overcome the factors that encourage land use change and institutional role improvement in farming is needed.